2017
DOI: 10.1016/j.neuroscience.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Preparatory cortical and spinal settings to counteract anticipated and non-anticipated perturbations

Abstract: Abstract-Little is known about how the central nervous system prepares postural responses differently in anticipated compared to non-anticipated perturbations. To investigate this, participants were exposed to translational and rotational perturbations presented in a blocked (anticipated) and a random (non-anticipated) design. The preparatory setting ('central set') was measured by H-reflexes, motor-evoked potentials (MEPs), and short-interval intracortical inhibition (SICI) shortly before perturbation onset i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…On the contrary, feedback control is characterized by the initiation of sufficient muscle responses after balance loss to compensate an unpredicted postural disturbance during one-legged standing and to avoid falling. In this respect, recent studies (Wälchli et al, 2017 ; Fujio et al, 2018 ) showed that the central nervous system differently prepares postural responses in expected compared to unexpected stance perturbations. For instance, Fujio et al ( 2018 ) examined motor-evoked potential (MEP) induced by transcranial magnetic stimulation during expected (via acoustic signal) and unexpected (no signal) perturbations, while standing on a moveable platform in healthy young adults (mean age: 27 ± 2 years).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, feedback control is characterized by the initiation of sufficient muscle responses after balance loss to compensate an unpredicted postural disturbance during one-legged standing and to avoid falling. In this respect, recent studies (Wälchli et al, 2017 ; Fujio et al, 2018 ) showed that the central nervous system differently prepares postural responses in expected compared to unexpected stance perturbations. For instance, Fujio et al ( 2018 ) examined motor-evoked potential (MEP) induced by transcranial magnetic stimulation during expected (via acoustic signal) and unexpected (no signal) perturbations, while standing on a moveable platform in healthy young adults (mean age: 27 ± 2 years).…”
Section: Discussionmentioning
confidence: 99%
“…Short interval intracortical inhibition (SICI) was measured by applying two TMS pulses with an interstimulus interval of 2.5 ms (Wälchli et al, 2017;Lauber et al, 2018) where the first conditioning pulse was subthreshold (0.7 AMT) and the second test pulse was suprathreshold (1.2 AMT). The conditioning pulse activates intracortical inhibitory interneurons and attenuates the MEP evoked by the second pulse which reflect excitability of the corticospinal neurons (Di Lazzaro & Rothwell, 2014).…”
Section: Short-interval Intracortical Inhibitionmentioning
confidence: 99%
“…Since the seminal findings of Horak et al ( 29 ), researchers have used more direct measures of corticospinal excitability and spinal reflex modulation to reveal the preparatory activity that occurs in spinal and cortical networks in advance of a predictable perturbation ( 33 ). Several electroencephalography studies have shown that prior to a predictable postural disturbance, a slow wave potential builds under central scalp electrodes ( 34 36 ).…”
Section: Predicting Instabilitymentioning
confidence: 99%
“…More recent studies have shown that this anticipatory cortical activity is similar regardless of whether the disturbance is self or externally induced ( 37 ) and it scales with the amplitude of the impending perturbation ( 32 ). Concurrent changes in the circuitry of the spinal cord accompany these anticipatory cortical potentials ( 33 ) implying that the purpose of this cortical activity may be to modify the “central set” or state of the nervous system ( 35 ), however, a causal relationship between the two remains to be defined.…”
Section: Predicting Instabilitymentioning
confidence: 99%
See 1 more Smart Citation